How the human resource (HR) function adds strategic value: A relational perspective of the HR function - Jo, Jinhwan; Chadwick, Clint; Han, Joo Hun (Human Resource Management, 2024)
AbstractIn the present article, we propose the concept of the HR function's relational activities and examine its influence on the firm's human capital resources (HCRs) and performance. Integrating insights from various streams of research in strategic human resource management (HRM) and strategic human capital, we develop a relational perspective of the HR function and propose the relational activities as the HR function's advisory and informative activities toward its internal stakeholders (i.e., line managers, employees, and senior managers) to help the stakeholders meet their goals and needs. In our framework, we theorize how the HR function's relational activities lead to superior firm performance by enhancing the firm's HCRs and identify the firm's strategic HR systems and human capital losses as factors that complement and necessitate the HR function's relational activities, respectively. Using a five‐wave, nationally representative panel dataset covering 1415 firm observations, we find robust support for our hypotheses: the HR function's relational activities were positively related to HCRs, which was more pronounced when coupled with high levels of strategic HR systems and human capital losses. The HCRs, in turn, transmitted the effects of the relational activities on the firm's subsequent operational and financial performance. Overall, these findings develop strategic HRM theory by contributing a more comprehensive conceptualization of the HR function's role in the strategic HRM process and by revealing its effects on firm performance along with key moderators.